Study on the performance of new cement-based underwater building crack repair materials based on response surface analysis - Ning Wang; Yinger Deng; Shuai Liu; Lin Chen (Scientific Reports)
Abstract In the process of repairing cracks in underwater buildings, the repair effect is not ideal due to the poor dispersion resistance and low retention rate of the slurry. In light of this, this study created a new magnetically driven cement-based (MDCGM) grouting material in this research that can be used to repair underwater building cracks. In this paper, a quadratic regression model was established with fluidity (X) as response values and bentonite content, water–cement ratio, Fe3O4 powder content, and flocculant content as influencing factors. The model has good fitting and reliability. Finally, the stone body’s damage constitutive equation under various damage factors is determined. This article focuses on the study of the fluidity of the slurry and the compressive strength of the stone body, and conducts an analysis of the microstructure. Meanwhile, it establishes the damage constitutive equation of the stone body. The results show that the primary and secondary relationships of the influence factors on the response value X are: Water-cement ratio > Flocculant content > Bentonite content > Fe3O4 content. The fluidity of the slurry is between 212.5 mm and 437.5 mm. When the water-cement ratio, the content of bentonite, and the content of the flocculant are 1%, 3%, and 5% respectively, as the content of Fe3O4 increases from 10 to 15% and 20%, the 3-day compressive strength of the grouted body increases by 6.02% and 33.40% respectively, and the 7-day compressive strength increases by 2.65% and 5.67% respectively. This indicates that Fe₃O₄ can significantly improve the compressive strength of the early-stage grouted body. The damage constitutive equation is consistent with the experimental results and can predict the mechanical properties of the stone body of the grouting material.